Feasibility Analysis of Sorgum Farming in Gorontalo Province - Siska Hulopi; Wawan K. Tolinggi; Ramlan Mustafa (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to: (1) determine the income earned by farmers from sorghum cultivation, and (2) assess the financial feasibility of sorghum farming in Gorontalo Province. The research was conducted from April to May 2025 and involved 20 farmers selected purposively. Data were collected through direct interviews using structured questionnaires, analyzed then quantitatively using several financial feasibility indicators, including total production cost, total revenue, net income, Gross Profit Margin (GPM), Net Profit Margin (NPM), and Revenue Cost Ratio (R/C). The results indicate that the average production cost per farmer per planting season was IDR 2,214,995, while the average revenue reached IDR 4,368,750. As a result, the average net income amounted to IDR 2,153,755. The R/C ratio of 1.9 confirms that sorghum farming is profitable, as every Rp. 1 of cost generates Rp. 1.9 of revenue. Furthermore, the GPM of 52.51% and NPM of 49.29% demonstrate a strong level of profitability. Based on these findings, sorghum farming in Gorontalo Province is considered financially viable and suitable for sustainable development.